Molecular ecology of the southern gray brocket deer (Mazama gouazoubira fischer, 1814) - González, Susana; Aristimuño, María Pía; Elizondo, Claudia; Bidegaray-Batista, Leticia; De Faria Peres, Pedro Henrique [UNESP]; Duarte, José Mauricio Barbanti [UNESP] (Springer Nature, 2020)
The gray brocket deer (Mazama gouazoubira Fisher 1814) hasawide distribution range throughout South America, inhabiting dense and continuous forests and open savannahs such as the Brazilian Cerrado, from the south of the Amazon River basin up to northern Argentina and throughout all of the forested areas in Uruguay. The gray brocket is a small to medium sized deer with a wide range of individual pelage colouration from dark gray to reddish brown. Due to its widespread distribution and the wide range of morphological variation, this species is an excellent model to examine the patterns of genetic variation and to explore if patterns of population genetic differentiation are correlated with historical distribution and ecology. The aim of this chapter is to provide an overview of the current state of knowledge of the gray brocket deer population dynamics, evolutionary patterns and demographic history obtained with morphologic, molecular, and ecological data. This Neotropical deer has retained high levels of genetic and morphological variation that could be correlated to an episode of demographic and geographic expansion in South America that likely occurred during the middle Pleistocene. Genetic analyses using mtDNA markers suggests that geographically separated subpopulations within the wide range of distribution of this species are acting as a metapopulation that has helped maintain remarkably high levels of genetic diversity. In spite of this high genetic diversity, the species could be endangered in the near future if habitat alteration and poaching continues. The signatures observed may only reflect the past demographic expansion and the genetic diversity with mtDNA markers reflecting only a shadow of the past overabundance of this species. Finally, we provide perspectives on how the application of novel next generation sequencing and niche modelling methodologies will magnify the power to contribute to the understanding of the potential extinction risks of cervid species and we propose future guidelines to design management and conservation strategies to better assess the conservation status of gray brocket deer populations in the Neotropics.
Keywords: Genetic diversity; Morphological variation; Neotropical biogeographic region